The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1001/jamaophthalmol.2018.3939
|View full text |Cite
|
Sign up to set email alerts
|

Association of Acute Endophthalmitis With Intravitreal Injections of Corticosteroids or Anti–Vascular Growth Factor Agents in a Nationwide Study in France

Abstract: The number of patients affected by retinal diseases treated with intravitreal injections (IVTs) has resulted in a rapidly growing number of procedures. One of the worst complications after these injections is endophthalmitis.OBJECTIVE To evaluate the incidence of acute endophthalmitis after IVTs of corticosteroids or anti-vascular endothelial growth factor (anti-VEGF) agents. DESIGN, SETTING, AND PARTICIPANTS This population-based cohort study included patients undergoing IVTs from January 1, 2012, through Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 48 publications
4
61
0
Order By: Relevance
“…Two large population-based studies have been published in recent years analyzing the endophthalmitis rate after intravitreal injection. 41,42 Baudin et al evaluated the incidence of acute endophthalmitis after intravitreal injection of corticosteroids or anti-VEGF agents in a nationwide study in France. Taking only the anti-VEGF injections into account, 1.67 million injections were evaluated from the French medical-administrative database.…”
Section: Intraocular Inflammation and Endophthalmitismentioning
confidence: 99%
See 2 more Smart Citations
“…Two large population-based studies have been published in recent years analyzing the endophthalmitis rate after intravitreal injection. 41,42 Baudin et al evaluated the incidence of acute endophthalmitis after intravitreal injection of corticosteroids or anti-VEGF agents in a nationwide study in France. Taking only the anti-VEGF injections into account, 1.67 million injections were evaluated from the French medical-administrative database.…”
Section: Intraocular Inflammation and Endophthalmitismentioning
confidence: 99%
“…The prefilled ranibizumab syringe therefore had decreased the rate of endophthalmitis by 40% compared with ranibizumab in a vial and by 46% for aflibercept in a vial. 41 Storey et al analysed 243 754 injections of ranibizumab in 10 centers in the USA (2016 to 2017) and Japan (2009 to 2017). 42 The suspected rate of endophthalmitis with an injection of ranibizumab in a vial was 0.026%, the rate of culture-positive endophthalmitis was 0.013%.…”
Section: Intraocular Inflammation and Endophthalmitismentioning
confidence: 99%
See 1 more Smart Citation
“…2 Baudin et al and our studies also found a 29% and 30% increased risk of endophthalmitis in women, repsectively. 1,2 These represent the first reports linking gender to endophthalmitis rates. Interestingly, despite age, gender and race almost uniformly being controlled for in other ophthalmic assessments (even when no demonstrable link exists to do so), gender has often been over-looked with regards to endophthalmitis after intravitreal injections.…”
mentioning
confidence: 93%
“…Two recent studies have provided several new interesting findings that further our understanding of the risk factors associated with post-injection endophthalmitis. 1,2 While these findings are novel to many of us, it is possible Genentech suspected this issue would arise as they have already received FDA approval and distributed pre-packaged syringes for both their 0.5mg(October 2016) and 0.3mg(March, 2108) doses of ranibizumab. Together, these studies offer compelling evidence that a policy mandating the sterile packaging of all intravitreal injections needs to be strongly considered.…”
mentioning
confidence: 99%